Kajian Media Pembelajaran Berdasarkan Kecenderungan Gaya Belajar Peserta Didik Sd/Mi - Mustafida, Fita (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
Achievement of learning depends on process learning that done. The determinant factor is teacher. Teacher has important role in the learning process in the school or Islamic School. Beside teacher, students also inflences, because student is the subject of learning. Because the essence of learning is a process of communicating; is the process of transferring message (Subject Matter) from the source of message (teacher) to the receiver (students). To avoid the fault in the transferring knowledge, neededa media to transferring message from the sender to the receiver that called by media of learning.By using media of learning suggested to makes more easily for student to receive knowledge well, so that there is no misunderstanding when receive the message from teacher. The ability of teacher to determine the media is very important and needed. Teacher must selective to determine the media of learning that used, because not all media of learning appropriate with condition. Teacher must choose media of learning that appropriate with context/needs, both of material and students.Keywords: Media of learning, Style of learning.